Upaya Strategis Pemerintah Mengatasi Masuknya Teroris Melalui Pelabuhan Gilimanuk Bali - Anak Agung Ayu Intan Parameswari; Ni Wayan Rainy Priadarsini S (Pusat Kajian Bali Universitas Udayana, 2023)
Today's deeds of terrorism are difficult to get rid of with the notion of radicalism which threatens state security. The tragedy of the Bali Bombing 1 in 2002 and 2 in 2005, sparked public concern that made the government must be more profound in strengthening the strict flow of entrances in every area, such as airports, terminals, and ports. This study aims to explain how the strategic security measures carried out by the Regional Government, especially Jembrana Regency as the owner of Gilimanuk Port access, which is directly adjacent to the island of Java, to overcome the entry of the threat of terrorism into Bali. This study uses a qualitative descriptive method with a human security framework. This research obtained an answer through a series of measures such as a series of policies in terms of legal instruments, a series of socialization in terms of a grass-roots approach, and formulating policies for the formation of a Conflict Team and the formation of an Early Awareness Team (Wasdin) equipped with a regional Wasdin Team and The Integrated Team for Handling Social Conflict. Furthermore, the Jembrana Regency Government is said to have been relatively good in foreseeing and overseeing terrorism issues in Bali, primarily in Gilimanuk Port.